2011
DOI: 10.1208/s12248-011-9316-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cyclosporine and Rifampin on the Pharmacokinetics of Macitentan, a Tissue-Targeting Dual Endothelin Receptor Antagonist

Abstract: Macitentan is a dual endothelin receptor antagonist under phase 3 investigation in pulmonary arterial hypertension. We investigated the effect of cyclosporine (Cs) and rifampin on the pharmacokinetics of macitentan and its metabolites ACT-132577 and ACT-373898 in healthy male subjects. In addition, in vitro studies were performed to investigate interactions between macitentan and its active metabolite ACT-132577 with human organic anion-transporting polypeptides (OATPs). The clinical study (AC-055-111) was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 61 publications
(69 citation statements)
references
References 19 publications
(26 reference statements)
5
61
0
1
Order By: Relevance
“…Our study illustrates how GLB plasma pharmacokinetics and distribution are largely governed by OATP transporters. RFA and CsA have a more pronounced inhibitory effect on OATP1A2, OATP1B1, and OATP1B3 than on OATP2B1 (13,(41)(42)(43)(44). In the present study, the organs in which […”
Section: In Situ Brain Perfusion In Micementioning
confidence: 53%
“…Our study illustrates how GLB plasma pharmacokinetics and distribution are largely governed by OATP transporters. RFA and CsA have a more pronounced inhibitory effect on OATP1A2, OATP1B1, and OATP1B3 than on OATP2B1 (13,(41)(42)(43)(44). In the present study, the organs in which […”
Section: In Situ Brain Perfusion In Micementioning
confidence: 53%
“…These conclusions were confirmed in a clinical drug-drug interaction study with cyclosporin A, an established potent inhibitor of OATP-mediated (Shitara et al, 2003) and NTCP-mediated transport (Mita et al, 2006). Concomitant cyclosporin A increased macitentan exposure in humans by only 1.1-fold (Bruderer et al, 2012a), compared with a 30-fold increase observed with the proven OATP substrate bosentan in the presence of cyclosporin A (Binet et al, 2000).…”
Section: Discussionmentioning
confidence: 67%
“…We have previously reported on the cellular uptake of macitentan in OATP1B1-and OATP1B3-overexpressing cells in the context of the clinical drug-drug interaction studies with cyclosporin A and rifampicin (Bruderer et al, 2012a). Table 1 summarizes these results of the uptake experiments with macitentan and ACT-132577 together with new data on OATP2B1.…”
Section: Resultsmentioning
confidence: 99%
“…data from phase I studies support a once-daily dosing regimen for macitentan and demonstrate that it can be taken irrespective of food intake and without drug-drug interactions with warfarin, sildenafil, ketoconazole or cyclosporine [20,21].…”
Section: Review: Pathways In Pah O Sitbon and Nw Morrellmentioning
confidence: 90%